The baby garden - Jafri, Adeeba (Goodword Books: New Delhi, 2008)
The story centers around a young child who learns about the creation of the world and the importance of nature and life. Through the metaphor of a garden, the book teaches children about the blessings of Allah and the interconnectedness of all living things. It emphasizes themes of gratitude, stewardship of the earth, and the beauty of Allah's creation.